Long-lived carriers-promoted photocatalytic deuteration of halides with D2O as the deuterium source over Cu doped quantum dots - Yang, Xian; Wang, Teng; Li, Yonglong; Hu, Yanfang; Wang, Ying; Xie, Wei (Journal of colloid and interface science, 2025)
Copper-doped cadmium sulfide quantum dots (Cu-CdS QDs) were used as photocatalysts for the deuteration of halides under visible-light irradiation, with D2O as the deuterium source. The combined experimental and theoretical calculation results reveal that long-lived carriers are produced by rapidly capturing photoinduced holes in the Cu-doped energy levels, which is beneficial for improving photocatalytic reactivity. [Display omitted] Deuterium labeling is a highly valuable yet challenging subject of research in various scientific fields. Conventional deuteration methods often involve harsh reaction conditions and suffer from limited reactivity and selectivity. Herein, we report a visible light–driven C–X (X = halogen) to C–D (D = deuterium) exchange strategy over copper-doped cadmium sulfide quantum dots (Cu-CdS QDs) under mild conditions, eliminating the need for noble metal catalysts and expensive deuterium sources. The conversion of aryl halides into deuterated products using Cu-CdS QDs reaches up to 99%, which is four times higher than that achieved using pristine CdS QDs. The substantial enhancement in the photocatalytic activity of the QDs can be primarily attributed to the generation of long-lived charge carriers (approximately 6 μs) induced by Cu doping. Mechanistic studies reveal that the Cu dopants considerably retard the recombination of photoinduced carriers by creating intermediate energy levels that serve as hole trapping centers in CdS QDs, thereby improving the electron utilization efficiency in energetically demanding photoreduction reactions. Additionally, the introduction of Cu increases the energy offset between the conduction band of CdS QDs and molecular acceptors, facilitating the electron transfer process. Upon visible light irradiation, a series of aryl halides can be efficiently converted into the desired deuterated compounds using D2O as the deuterium source. This work demonstrates that regulating charge carrier dynamics in ultrasmall QD-based photocatalysts is a promising strategy for promoting organic transformations.